Proceedings of the the 3rd International Conference on Advance &Amp; Scientific Innovation 2020
DOI: 10.4108/eai.20-6-2020.2300711
|View full text |Cite
|
Sign up to set email alerts
|

Historical Gossip As Social Engineering To Build Historical Awareness

Abstract: The main objective of social engineering trough historical gossip is to produce new knowledge, attitude and new historical awareness to Manyak Payed community of Aceh Tamiang Regency. This effort needs to be done to strengthen national integration. This technique is applied with historical gossip media on the local history object that intersects with the national history of Indonesia. The aforementioned Historical Object is the Expansion of Majapahit and a figure named Gajah Mada in Aceh Tamiang. The social en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…And the results of the validity test give a good value for student achievement. 17 The results of other studies related to the application of the SAVI-based learning model have a good effect on student learning outcomes in the first semester of class VIII at MTs Negeri 2 Bandar Lampung. 18 Research by Sholihah et al 19 in applying the SAVI learning model to fourth-grade students showed an increase in speaking skills.…”
Section: Introductionmentioning
confidence: 95%
“…And the results of the validity test give a good value for student achievement. 17 The results of other studies related to the application of the SAVI-based learning model have a good effect on student learning outcomes in the first semester of class VIII at MTs Negeri 2 Bandar Lampung. 18 Research by Sholihah et al 19 in applying the SAVI learning model to fourth-grade students showed an increase in speaking skills.…”
Section: Introductionmentioning
confidence: 95%